Sistematización del 54° Festival de Teatro de Manizales (2024)
The present work seeks to detail relevant aspects within the learning and experiences of the master artists in training of the Bachelor of Performing Arts who participated in the experience of the 54th International Theater Festival in Manizales 2022. Implementing the interpretive approach proposed by Manuel Baeza, the which speaks of the understanding between the other and one's own, but finally the latter (one's own) is the one who synthesizes. Therefore, this research is based on gathering the opinions of five of the subjects of the degree and the master artist in training as an interpreter of the information of the experience, who were immersed in this entire training process, making conclusions that contribute to the importance of carrying out the artistic pedagogical experience